2022
DOI: 10.1155/2022/4834594
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Enhanced Magnetic Resonance Imaging versus Ultrasonic Diffused Optical Tomography in Early Diagnosis of Breast Cancer

Abstract: Objective. To compare the application value of dynamic enhanced magnetic resonance imaging (MRI) and ultrasonic diffused optical tomography (DOT) in early diagnosis of breast cancer. Methods. The clinical data of 110 female patients with breast diseases treated in our hospital from June 2018 to June 2021 were selected for the retrospective analysis, and the patients were divided into the benign lesion group (n = 50) and breast cancer group (n = 60) according to the pathologic findings. All patients received dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In biological tissue, the integrity of the cell membranes and the cell density of tissues are negatively correlated with the degree of water diffusion. As breast tumors have intact cell membranes and high cell density, the movement of water molecules is restricted; thus, the tumors present high signals in DWI images and low signals in ADC images ( 27 , 28 ). The changes of vascular distribution and lesion size were later than the changes of ADC value, and useful information about early breast cancer can be obtained from ADC images.…”
Section: Discussionmentioning
confidence: 99%
“…In biological tissue, the integrity of the cell membranes and the cell density of tissues are negatively correlated with the degree of water diffusion. As breast tumors have intact cell membranes and high cell density, the movement of water molecules is restricted; thus, the tumors present high signals in DWI images and low signals in ADC images ( 27 , 28 ). The changes of vascular distribution and lesion size were later than the changes of ADC value, and useful information about early breast cancer can be obtained from ADC images.…”
Section: Discussionmentioning
confidence: 99%
“…The breast imaging reporting and date system formulated by the American College of Radiology provided classification criteria for the ultrasound diagnosis of breast diseases (10). There are many clinical diagnostic methods, including nuclear magnetic resonance, tomography, threedimensional reconstruction technology, and ultrasound examination (11)(12)(13)(14)(15). In some cases, due to the limited availability of medical imaging equipment, as well as the less working experience of physicians, misdiagnosis still occurs sometimes, leading to a patient's failure to be diagnosed correctly (16).…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled "Dynamic Enhanced Magnetic Resonance Imaging versus Ultrasonic Difused Optical Tomography in Early Diagnosis of Breast Cancer" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Dynamic Enhanced Magnetic Resonance Imaging versus Ultrasonic Diffused Optical Tomography in Early Diagnosis of Breast Cancer” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%